2005
DOI: 10.1086/429964
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interleukin‐10 onAspergillus fumigatusInfection in Patients with Cystic Fibrosis

Abstract: Recent evidence suggests that genetic polymorphisms that affect the production of interleukin (IL)-10 may play a role in the response to pathogens in cystic fibrosis (CF). The present study was designed to investigate a possible association between alleles carried at position -1082 in the promoter region of the IL-10 gene and clinical data on 378 patients with CF. After adjustment for potential confounding variables, a significant relationship was found between the -1082GG genotype and both colonization with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 15 publications
3
54
0
1
Order By: Relevance
“…We found that the percentage of colonized patients was higher among homozygous for GG at -1082 compared to subjects carrying the -1082AA genotype, and that the high-IL-10-producing haplotype GCC was associated with a greater risk of P. aeruginosa airway colonization (Table 4). This seems to be consistent with the results of Brouard et al [19], who showed a significant relationship between the -1082GG genotype and colonization with Aspergillus fumigatus in CF patients. Furthermore, other association studies of IL-10 gene polymorphisms with infectious lung diseases have shown a correlation between the same -1082GG genotype and the severity of community-acquired pneumonia and pneumococcal infection in hospitalized patients [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…We found that the percentage of colonized patients was higher among homozygous for GG at -1082 compared to subjects carrying the -1082AA genotype, and that the high-IL-10-producing haplotype GCC was associated with a greater risk of P. aeruginosa airway colonization (Table 4). This seems to be consistent with the results of Brouard et al [19], who showed a significant relationship between the -1082GG genotype and colonization with Aspergillus fumigatus in CF patients. Furthermore, other association studies of IL-10 gene polymorphisms with infectious lung diseases have shown a correlation between the same -1082GG genotype and the severity of community-acquired pneumonia and pneumococcal infection in hospitalized patients [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…This is particularly of concern as certain studies have revealed possible associations between alleles in the IL-10 promoter region responsible for higher IL-10 secretion and A. fumigatus colonization of lung. 65 These potential toxicities indicate that caution must be exercised in considering clinical applications of the potent immunomodulatory effects of rAAV1-IL-10, which might otherwise be therapeutic in a number of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Specifi c genetic factors have been implicated in the development of this entity. IL-10 overproduction, as conferred by the -1082GG genotype in the promoter region of the IL10 gene, signifi cantly increases the risk of colonization with A. fumigatus and the development of ABPA [9]. Further genotype analyses of patients with ABPA revealed a strong association with HLA-DR2 and HLA-DR5 alleles, whereas the HLA-DQ2 allele appears to protect against the disorder [10].…”
Section: Immunopathogenesismentioning
confidence: 96%